OPTIMAL ROBUST WIDE SPEED CONTROL OF INDUCTION МACHINE - Potapenko, E.M.; Shiyka, A.A. (Radio Electronics, Computer Science, Control, 2013)
This paper represents a robust voltage regulation algorithm for an induction machines that enable minimization of the losses and maximization of torque capability. The maximum torque of an induction machine is limited by the current and voltage constraints. Depending on rotor speed, current and voltage limits, the algorithm calculates the coupling coefficient of stator currents k, that determines the optimal stator currents (id, iq) for the maximum torque capability in whole values of the rotor speed (under the rotor base speed and in the field-weakening region). If those limits are not reached, the algorithm calculates optimal stator currents for minimization of losses of an induction machine. The block diagram of robust optimal voltage regulator is represented. The validity of proposed algorithm is demonstrated by simulation.